2022
DOI: 10.3389/fnbeh.2022.970291
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for long-term potentiation mechanisms in the maintenance of object recognition memory in perirhinal cortex revealed by the infusion of zeta inhibitory pseudosubstrate

Abstract: Object recognition, the ability to discriminate between a novel and a familiar stimulus, is critically dependent upon the perirhinal cortex. Neural response reductions upon repetition of a stimulus, have been hypothesized to be the mechanism within perirhinal cortex that supports recognition memory function. Thus, investigations into the mechanisms of long-term depression (LTD) in perirhinal cortex has provided insight into the mechanism of object recognition memory formation, but the contribution of long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…We found that this intervention impairs the expression of recognition memory for novel objects, but not novel object locations, for both recent (1 day old) as well as remote (6 days old) memories. We thus replicate the findings of Outram et al (2022) , lending strong support to our respective results. Together with our earlier demonstration that infusing ZIP into the dorsal hippocampus disrupts long-term object location but not object identity memory, these data show that long-term memory for what has been encountered requires representations in perirhinal cortex, while memory for where things had been placed requires representations in dorsal hippocampus ( Winters, 2004 ; Forwood et al, 2005 ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We found that this intervention impairs the expression of recognition memory for novel objects, but not novel object locations, for both recent (1 day old) as well as remote (6 days old) memories. We thus replicate the findings of Outram et al (2022) , lending strong support to our respective results. Together with our earlier demonstration that infusing ZIP into the dorsal hippocampus disrupts long-term object location but not object identity memory, these data show that long-term memory for what has been encountered requires representations in perirhinal cortex, while memory for where things had been placed requires representations in dorsal hippocampus ( Winters, 2004 ; Forwood et al, 2005 ).…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, these data suggest that processes underpinning LTD also promote object recognition memory in perirhinal cortex. Our data, as well as the findings from Outram et al (2022) , however, indicate that forms of synaptic plasticity involved in LTP also are critical for object recognition memory in this brain region. Specifically, the results of Outram et al (2022) show that the amnesic effects of ZIP on object recognition memory involve the internalization of GluA2/AMPARs, suggesting that maintaining long-lasting object recognition memory depends on forms of synaptic plasticity that are critical for LTP, but not LTD.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations